2012
DOI: 10.1002/j.2055-2335.2012.tb00167.x
|View full text |Cite
|
Sign up to set email alerts
|

Combined Neem Oil 6% w/w and Eucalyptus Oil 16% w/w Lotion for Treating Head Lice: In Vitro and In Vivo Efficacy Studies

Abstract: Aim: To test a combined neem oil 6% w/w and eucalyptus oil 16% w/w lotion for the whole-of-life cycle treatment of human head lice (Pediculus humanus var. capitis) infestation. Method: Preliminary formulations of dilutions of neem and eucalyptus oils in isopropanol were tested for pediculicidal and ovicidal efficacies against Pediculus humanus var. capitis. This trial informed the development of a stable formulation consisting of neem oil 6% w/w and eucalyptus oil 16% w/w in a hydrophobic carrier (mixture of l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…One shampoo from Germany based on a concentrated extract has undergone investigations in villages in Egypt and Arabia (Heukelbach et al 2006;Abdel-Ghaffar and Semmler 2007;Schmahl et al 2010;Mehlhorn et al 2011;Abdel-Ghaffar et al 2012) with reported high efficacy following a single application. In contrast, an alcohol-based Australian product, containing 6% neem oil and 16% eucalyptus, required two applications plus combing in a Thai study (Thawornchaisit et al 2012). However, both results contrast strongly with our earlier low success using a neem oil-based conditioner plus combing (Brown and Burgess 2017).…”
Section: Introductionmentioning
confidence: 99%
“…One shampoo from Germany based on a concentrated extract has undergone investigations in villages in Egypt and Arabia (Heukelbach et al 2006;Abdel-Ghaffar and Semmler 2007;Schmahl et al 2010;Mehlhorn et al 2011;Abdel-Ghaffar et al 2012) with reported high efficacy following a single application. In contrast, an alcohol-based Australian product, containing 6% neem oil and 16% eucalyptus, required two applications plus combing in a Thai study (Thawornchaisit et al 2012). However, both results contrast strongly with our earlier low success using a neem oil-based conditioner plus combing (Brown and Burgess 2017).…”
Section: Introductionmentioning
confidence: 99%